1996
DOI: 10.1007/bf01718333
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of humoral immune response to the major structural proteins of the porcine reproductive and respiratory syndrome virus

Abstract: The kinetics of appearance of antibodies directed to the major structural proteins N, M and E of porcine reproductive and respiratory syndrome virus (PRRSV) was followed in pigs naturally- and experimentally-exposed to the virus. Specific IgM antibody titers were first detected by indirect immunofluorescence (IIF) at the end of the first week of PRRSV infection, peaked by day 14 to 21 post-inoculation (p.i.), then rapidly decreased to undetectable levels by day 35 to 42 p.i. On the other hand, specific IgG ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
112
3
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(128 citation statements)
references
References 18 publications
7
112
3
1
Order By: Relevance
“…The VN antibodies response detected at 10 days post-challenge was the specific consequence of prior immunization with hAdV/synORF5 since normally, VN antibodies are detected after only 3 to 4 weeks in SPF pigs experimentally-or naturallyinfected with PRRSV [10,20]. The higher reactivity to GP5, as well as the higher VN activity of pigs sera that have been vaccinated either with hAdV/wtORF5 or hAdV/synORF5 is in agreement with previous findings indicating that GP5 is the primary structural glycoprotein of PRRSV involved in virus neutralization activity [6,7,25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The VN antibodies response detected at 10 days post-challenge was the specific consequence of prior immunization with hAdV/synORF5 since normally, VN antibodies are detected after only 3 to 4 weeks in SPF pigs experimentally-or naturallyinfected with PRRSV [10,20]. The higher reactivity to GP5, as well as the higher VN activity of pigs sera that have been vaccinated either with hAdV/wtORF5 or hAdV/synORF5 is in agreement with previous findings indicating that GP5 is the primary structural glycoprotein of PRRSV involved in virus neutralization activity [6,7,25].…”
Section: Discussionmentioning
confidence: 99%
“…Following an incubation period of 24 and 48 h post-infection, those hAdVs infected cells were fixed with a 80% cold acetone solution for 20 min at 4 o C and the IIF was done using a 1/200 dilution of the α5 serum as previously described [20].…”
Section: Indirect Immunofluorescence Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The ELISA most likely detects ORF 7 and 6 epitopes, which are the most abundant antigens in the virion, whereas the WB only detects a specific antibody to ORF 5 product. Two research studies have demonstrated that the ORF 5 product is underpresented in virus preparations grown in tissue culture 12,18 making the ELISA inherently less sensitive than the WB assay. As previously reported, 12 the antibodies to recombinant ORF 5 product could be demonstrated as early as 6 days PI, whereas antibody to ORFs 6 and 7 could only be detected by the end of the week 2 PI.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a high molar ratio of ORF 7 and 6 proteins, relative to ORF 4 and 5 proteins, is found in the virion. 12,18 Antibodies to ORF 5 protein appear to be major serologic markers in PRRSV-infected pigs. This finding is based on the detection of antibodies by Western blotting (WB) over a period of 150 days in infected animals (unpublished data).…”
mentioning
confidence: 99%